An Idiot's Guide to Prioritization in the Health Sector - Yazbeck, Abdo S. (World Bank, Washington, DC, 2013)
Every year, Ministries of Health the world over develop annual budgets for the health sector. Every year, donors, academicians, advocacy groups, medical trade unions and professional organizations, and health service managers and providers complain that the budgets have the wrong priorities. While all these groups are united in their unhappiness with the priorities reflected in these budgets, they disagree on what the priorities should be and on how the prioritization process should be conducted. A review of the published literature reveals a lack of consensus in the policy and academic communities on how best to prioritize health sector budgets. What is more surprising is that the literature review reveals little documentation on how countries actually do prioritize health expenditures. This paper attempts to address both gaps in information about prioritization. The first part of the paper describes hat goes into a prioritization exercise. This typically includes advocates, prioritization criteria, and methodologies for making choices. The first part also describes the analytical tools available to understand who gains and who loses from decisions taken in developing a budget for the health sector. The second part of the paper documents and actual prioritization exercise undertaken in Bangladesh between the years 1996 and 1999. As the title of this paper indicates, this is not a theoretical or academic paper. It is simply meant to empower potential practitioners by introducing them to the players involved in the process, the techniques utilized by these players, the political realities that drive the process, and some evaluation techniques.